Isolation Of Bacteriocinogenic Lactic Acid Bacteria And Purification Of Selected Bacteriocins From Traditional Fermented Foods - Lim, Yin Sze (2003)
A variety of bacteriocins have been discovered, however there is limited information on their physico-chemical, biochemical and genetic characteristics. This study was carried out to isolate bacteriocinogenic lactic acid bacteria (LAB) from local fermented foods (Tempeh, Tapai Ubi and Tapai Pulut) and food condiment (Chili Bo). Selected bacteriocinogenic isolates and the bacteriocins produced were then characterized. The bacteriocins were purified using Fast Protein Liquid Chromatography (FPLC). Among 55 isolates isolated from the fermented foods, 20 of the isolates were able to produce bacteriocins in the range of 200-800 AU/ml inhibitory activity. Bacteriocins produced by UL4, UB6 and GB5 were tested against selected gram-positive and -negative pathogens. Isolate UL4, which produced the highest antagonistic activity against Pediococcus acidilactici, Enterococcus faecalis, Enterococcus faecium and Listeria monocytogenes was selected for further characterization. The isolate UL4 was identified as Lactobacillus plantarum I using API 50 CHL test kit. Lb. plantarum I-UL4 is a gram-positive cocco-bacilli facultative anaerobe. The maximum bacteriocin production of 800 AU/ml was achieved after 12 h incubation at 30°C in neutralized MRS medium. The bacteriocin UL4 was characterized physico-chemically and classified as Class IT, heat stable bacteriocin, since it was able to maintain 200 AU/ml bacteriocin activity after being autoclaved at 121°C for 15 min. Bacteriocin UL4 was also able to tolerate a broad pH range, from acidic pH 2-5 to basic pH 7-8. Bacteriocin UL4 was suitable to be applied in refrigerated foods due to its stability at temperature below 15°C for 45 days.